Jatabeko intonazioaz - Gaminde, Iñaki (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2000)
In the present work the author describes the main enunciation models of the Basque from Jatabe. At the beginning of the work the author represents the characteristics of the Jatabe accent, so as to bear them in mind better, and then carries out a phonological analysis of a corpus of declaratory phrases specifically prepared for their analysis. Mainly it is accomplished the sentences analysis composed by simple syntagmas, complex syntagmas and syntagmas of marked words. After the phonological analysis is finished, the phonetic analysis of the tones is then carried out. Finally, questions of the yes/no, who/what and other types are analysed.